THE MODERATING ROLE OF PEER SOCIAL SUPPORT ON THE EFFECT OF SELF-CONTROL ON ACADEMIC PROCRASTINATION - Zabar, Muhamad Abdul; Gumilar, Gugum; Nurdianti, Raden Roro Suci (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
This study aims to analyze the moderating role of peer social support on the effect of self-control on student academic procrastination. The study used a quantitative approach with an explanatory survey method. The research sample involved 221 students of the Economics Education Department of Siliwangi University in the 2024/2025 academic year who were taken using proportional stratified sampling techniques. Data collection was carried out through a questionnaire with a Likert scale. Data analysis using Moderated Regression Analysis (MRA). The results showed that: (1) self-control has a significant negative effect on academic procrastination with a regression coefficient of -0.435 at a significance level of 0.001 <0.05; (2) peer social support acts as a pure moderator in the relationship between self-control and academic procrastination, with an interaction coefficient of -0.017 at a significance level of 0.002 <0.05; (3) simultaneously, self-control, peer social support, and their interaction have a significant effect on academic procrastination with a calculated F value of 7.272 at a significance level of 0.000 <0.05. This study contributes to the development of interventions to reduce academic procrastination by considering internal and external factors of students